Aplicación Móvil de Realidad Aumentada para la Enseñanza de la Clasificación de los Seres Vivos a Niños de Tercer Grado - Solano, Cesar Augusto; Casas Díaz, Johan Fabiel; Guevara Bolaños, Juan Carlos (Ingeniería, 2015)
The Information and Communication Technologies (ICT) have had an important development in recent years with promising results in supporting learning processes in the classroom . For this reason, it is important to create innovative tools to motivate teachers and students to use these kind of technologies both inside and outside the classroom. This paper describes the development of a tool in this direction, aimed at helping students of third grade of primary school in learning classification of living beings aided with Augmented Reality (AR) techniques. Additionally an evaluation model is proposed to measure the impact of the software.